An Asynchronous Software Inspection Model - Ahmed Nwesri, Abdusalam F.; Ahmad, Rodina (Malaysian Journal of Computer Science, 2000)
This paper introduces an inspection model that discharges face-to-face meetings among inspectors in the software development group. The model aims at the elimination of the synchronous inspection meeting and the reduction of the asynchronous meeting by filtering out minor defects through the use of incontrovertible voting before the asynchronous meeting. The model goes through eight phases: initiation, overview, private checking, public checking, correlation, explicit voting, asynchronous meeting and rework and follow-up. The model is supported by a web-based tool named WASIT.